The relation of some playing positions with maximum aerobic speed for football players - Chaib, yasser; Guesmi, Abdelmalek (Journal of Human Sciences, 2022)
The soccer player must be characterized by a high degree of physical fitness to be able to carry out physical, skill and tactical tasks. The maximum aerobic speed is one of the most important fitness requirements that a soccer player needs. The foot is considered the indicator of physical fitness and its first weapon That is why we wanted to stand on the importance of the maximum aerobic speed and its close relationship to determine the playing position of football players under 19 years old, by applying the vameval test on a sample represented in the middle class of the Esperance Barcaforage teams and the Batna University team with an average of 20 players from both teams distributed with 6 players in defense from Each team and 4 players in the middle of each team, the results were as follows:There is no statistically significant difference in the maximum air speed between the playing positions in the middle of the field among the sample members There is no statistically significant difference in the maximum aerobic speed between the playing positions in defense among the sample members.